Broadband internet and social capital - Andrea Geraci; Mattia Nardotto; Tommaso Reggiani; Fabio Sabatini (Cardiff University, Cardiff Business School, 2021)
We study the impact of broadband penetration on social capital in the UK. Our empirical strategy exploits a technological feature of the telecommunication infrastructure that generated substantial variation in the quality of Internet access across households. The speed of a domestic connection rapidly decays with the distance of a user's line from the network's node serving the area. Merging information on the topology of the network with geocoded longitudinal data about individual social capital from 1997 to 2017, we show that access to fast Internet caused a significant decline in civic and political engagement. Overall, our results suggest that broadband penetration crowded out several dimensions of social capital.
Keywords: D91; L82; Z13; 330; ICT; broadband infrastructure; networks; Internet; social capital; civic capital